Bulgaria interbelică în umbra celor două catastrofe naționale - Iskra BAEVA (Polis: Revista de Stiinte Politice, 2022)
In this study, the author’s approach was to review the most important moments of political history, which the Bulgarian state experienced from 1877-1878 until the end of the Second World War. As Baeva introduces us, Bulgarian democracy has been influenced by the geo-political and economic realities of the time. The incomplete realization of the Bulgarian nation-state and the existence of a deeply rural society were the two constants that inexorably influenced the internal and foreign policy of the Bulgarian political class during the analyzed period.